Are immunosuppressant related to unfavorable outcomes in patients COVID-19 with autoimmune rheumatic disease?: A review of clinical evidence - Oki Nugraha Putra; Hardiyono Hardiyono; Mia Arum Anggraini (Faculty of Pharmacy, Mahidol University, 2022)
The impact of immunosuppressant therapy in COVID-19 patients with autoimmune rheumatic disease remains unclear based on previous studies. Here, we reviewed the clinical evidence to evaluate COVID-19 patients with rheumatic disease outcomes, which previously used immunosuppressant therapy to control the disease. We used PubMed and Science Direct database to search literature up to April 2021 for publications with confirmed COVID-19 infection with rheumatic disease. The outcomes of this review were the infection rate of COVID-19 and the rate of hospitalization, ICU admission, and mortality. A total of 16 articles were included in this review. The overall rates of COVID-19 infection in patients with autoimmune rheumatic disease did not differ from the general population. Rheumatic disease patients who previously used hydroxychloroquine showed a similar infection risk of COVID-19 with those who did not use hydroxychloroquine. Furthermore, immunosuppressant therapies were associated with poor clinical outcomes, increase risk of hospitalization, ICU admission, and mortality, particularly in patients with comorbidities. The use of bDMARD, such as TNF-? inhibitor, showed a protective effect to reduce the risk of hospitalization and mortality. The administration of immunosuppressant therapy must be closely monitored in rheumatic disease patients due to unfavorable outcomes. More studies are urgently required to map risk factors of clinical outcomes with the specific immunosuppressant therapy and specific rheumatic disease.